Lessons from history for V˙O2max and the V˙O2 plateau, part 1, 1920 – 1961: original concepts were based on discontinuous exercise protocols - Robergs, Robert A.; O’Malley, Bridgette; Torrens, Sam; McNulty, Craig Ryan; Titheradge, Praneel; Baker, Julien S.; Astorino, Todd A.; Green, Simon; Nalos, Marek (Frontiers in Physiology, 2025)
PurposeThe maximal rate of oxygen uptake (V˙O2max) has an early history (1920–1961) based on discontinuous incremental exercise protocols. Regardless, debate continues on many sub-topics and methodologies involved in this measure. There could be lessons to learn about the relevance, or not, of content within the accumulating knowledge of this topic if there is a detailed account of the research of this time-period.MethodsManuscript references were retrieved from PubMed and Google Scholar for the targeted topics and time-period.ResultsIn 1923 and 1924, Hill proposed that during discontinuous incremental exercise bouts, there is eventually a levelling in V˙O2 despite increasing exercise intensity or sustained effort. Subsequent researchers in the 1950’s described this ‘levelling in V˙O2’ observation as a plateau, which functioned to verify V˙O2max. However, when critiquing the data from studies with valid methodology, evidence of a V˙O2 plateau at or near V˙O2max was only seen in a subset of participants in 1924 (2 of 7), with added evidence in 1959 (2 of 4) and 1961 (4 of 5). Collectively, 50% of the subjects were unable to attain a V˙O2 plateau response at V˙O2max.ConclusionDespite major limitations to the published research and data interpretations prior to 1961, such work led to the incorrect (not evidence-based) expectation that all participants should demonstrate a V˙O2 plateau at or near V˙O2max. The inter-connectedness of V˙O2max and the V˙O2 plateau concepts thereby became engrained into the pre-1970s, and perhaps later, epistemology of exercise physiology.